Access over 35 million academic & study documents

2(c d)+(c 3d) 5(c d)answer should be 6c + 4dSolution 2(c

Content type
User Generated
Rating
Showing Page:
1/1
-2(c-d)+(c-3d)-5(c-d)
answer should be -6c + 4d
Solution
-2(c-d)+(c-3d)-5(c-d)
=-2c+2d+c-3d-5c+5d
=-2c+c-5c+2d-3d+5d
=-6c+4d

Sign up to view the full document!

lock_open Sign Up
Unformatted Attachment Preview
-2(c-d)+(c-3d)-5(c-d) answer should be -6c + 4d Solution -2(c-d)+(c-3d)-5(c-d) =-2c+2d+c-3d-5c+5d =-2c+c-5c+2d-3d+5d =-6c+4d Name: Description: ...
Purchase document to see full attachment
User generated content is uploaded by users for the purposes of learning and should be used following Studypool's honor code & terms of service.

Anonymous
Really helped me to better understand my coursework. Super recommended.

Studypool
4.7
Indeed
4.5
Sitejabber
4.4